The Impact of Corporate Governance Compliance on Transparency in Malaysian Stock Market - Ghaderi, Ebrahim Baba (2010)
The first objective of this study is to examine the extent of corporate governance compliance among a sample of 100 companies listed on the Bursa Malaysia. The study also empirically investigates the relationship between the extent of corporate governance compliance and on the extent of voluntary disclosure is examined. In order to compare the results of this study with other studies on voluntary disclosure, a number of control variables (firm size and leverage) are included in the regression model.